Reconfigurable Unidirectional Photonic Crystal Using Liquid Crystal Layer - Aya El-metwally; Nihal F. F. Areed; Mohamed Farhat O. Hameed; Salah S. A. Obayya (IEEE Photonics Journal, 2017)
Reconfigurable unidirectional transmission based on the nematic liquid crystal (NLC) layer and 2-D photonic crystal (PhC) platforms is presented and simulated. The suggested one way transmission can be tuned at different wavelengths based on the NLC biasing state. A comprehensive parametric study using plane wave expansion and finite difference time domain (FDTD) methods has been carried out for explaining and optimizing the performance of the proposed structure. The transmission spectra calculations reveal that the reported structure can perform nearly perfect isolation at two different bands (1406–1412 nm and 1416–1421 nm) with an average contrast ratio (Cr) of about 36.9 dB. The investigated unidirectional PhC structure has advantages in terms of compactness and reconfigurability and can be used efficiently in ultrahigh nanoscale integrated circuits.